AN ANALYSIS OF FARMER HOUSEHOLD FOOD SECURITY: CASE STUDY IN PATUK VILLAGE, WAJAK, MALANG REGENCY - Mayang Adelia Puspita; nuhfil Hanani (Agricultural Socio-Economics Journal, 2017)
Food security is a priority in Indonesia at this time specially to achieve food security of households to reduce food-insecure communities. According Sumarwan and Sukandar (1998), household food security and household welfare can be determined from the aspect of Adequacy Rate of Energy (ARE) and Adequacy Rate of Protein (ARP). This paper presented (1) the food security situation among farmer households in Patuk Village using Adequacy Rate of Energy (ARE) (2) factors affecting Adequacy Rate of Energy (ARE) of farmer household. Primary data were used in this study and these were obtained using in-depth interview and 2x24 food recall survey to measure farmer household food pattern. The analytical tools used include tables, percentages and analyzed using 2-SLS regression model. The result showed that 18.75% were very food secure, 21.88% were food secure enough and the rest 59.38% were food insecure. From these results, it can be seen that the majority of the farmer household in this study still food insecure. Based on the regression analysis method, the result shows that the adequacy rate of energy is positively related to the value of food consumption, mother education level, income per capita, and negatively related to the value of non-food consumption.